8 Stimulation of calcium sparks in both sino – atrial node and ventricular myocytes. (17th November 2015) - Miller, L; Steele, DS; Greensmith, DJ; Hart, G; Dobrzynski, H; Boyett, MR
Abstract : In ventricular myocytes (VMs), Ca sparks relieve the SR from Ca overload (during diastole) and triggered sparks form the systolic Ca transient. In sinoatrial node myocytes (SANCs), Ca sparks regulate pacemaker automaticity. Ca spark characteristics in both cell types were assessed and β-adrenergic receptor (β-AR) stimulation responsiveness was compared. Myocytes were isolated from hearts from adult male Wistar rats. Procedures were in accordance with the Animals (Scientific Procedures) Act 1986. Changes in [Ca 2+ ]i were detected by fluo-8 AM. Isoprenaline (ISO) was applied at 100 nM. Analysis was performed using xySpark. Mean data (VMs vs SANCs): Ca spark amplitude (ΔF/F0), 0.33 ± 0.02 vs 0.64 ± 0.03 (p < 0.05); spark frequency (sparks 1000 µm –1 s –1 ), 9.41 ± 2.02 vs 33.4 ± 4.4 (p < 0.05); spatial width, 2.71 ± 0.1 vs 2.59 ± 0.1 µm; spark duration (ms), 31.35 ± 2.7 vs 47.65 ± 4.3 (p < 0.05) and spark mass (ΔF/F0 µm 3 ), 10.52 ± 0.98 vs 14.68 ± 2.44. Following ISO, VMs; Ca spark amplitude and spark mass; increased by 34.4 ± 12% and 10 ± 1% respectively; spark duration: decreased by 17 ± 4% (p < 0.05, n = 10). SANCs; spark frequency, increased by 47 ± 19%; spark mass by 49.2 ± 24.0% (p < 0.05, n = 11). A greater SR-Ca release occurs during Ca sparks in SANCs vs VMs; facilitating acceleration of the DD phase of the SAN action potential. β-AR stimulation enhances VM Ca sparks and increases SANC spark frequency and mass; therefore facilitating the increased chronotropic effects on the cardiac pacemaker during β–AR stimulation.